Decreased glycolytic metabolism in non-compaction cardiomyopathy by 18F-fluoro-2-deoxyglucose positron emission tomography: new insights into pathophysiological mechanisms and clinical implications. (30th March 2017) - Tavares de Melo, Marcelo Dantas; Giorgi, Maria Clementina Pinto; Assuncao, Antonildes Nascimento; Dantas, Roberto Nery; Araujo Filho, Jose de Arimateia; Parga Filho, Jose Rodrigues; Bierrenbach, Ana Luiza de Souza; de Lima, Camila Rocon; Soares, José; Meneguetti, José Claudio; Mady, Charles; Hajjar, Ludhmila Abrahão; et al.
Abstract: Aims: The pathophysiological mechanisms of left ventricular non-compaction cardiomyopathy (LVNC) remain controversial. This study performed combined 18 F-fluoro-2-deoxyglucose dynamic positron emission tomography (FDG-PET) and 99m Tc-sestamibi single-photon emission computed tomography (SPECT) studies to evaluate myocardial glucose metabolism and perfusion in patients with LVNC and their clinical implications. Methods and results: Thirty patients (41 ± 12 years, 53% male) with LVNC, diagnosed by cardiovascular magnetic resonance (CMR) criteria, and eight age-matched healthy controls (42 ± 12 years, 50% male) were prospectively recruited to undergo FDG-PET with measurement of the myocardial glucose uptake rate (MGU) and SPECT to investigate perfusion-metabolism patterns. Patients with LVNC had lower global MGU compared with that in controls (36.9 ± 8.8 vs . 44.6 ± 5.4 μmol/min/100 g, respectively, P  = 0.02). Of 17 LV segments, MGU levels were significantly reduced in 8, and also a reduction was observed when compacted segments from LVNC were compared with the segments from control subjects ( P  < 0.001). Perfusion defects were also found in 15 (50%) patients (45 LV segments: 64.4% match, and 35.6% mismatch perfusion-metabolism pattern). Univariate and multivariate analyses showed that beta-blocker therapy was associated with increased MGU (beta coefficient = 10.1, P  = 0.008). Moreover, a gradual increase occurred in MGU across the beta-blocker dose groups ( P for trend = 0.01). Conclusion: The reduction of MGU documented by FDG-PET in LVNC supports the hypothesis that a cellular metabolic pathway may play a role in the pathophysiology of LVNC. The beneficial effect of beta-blocker mediating myocardial metabolism in the clinical course of LVNC requires further investigation.